2012
DOI: 10.5194/nhess-12-1277-2012
|View full text |Cite
|
Sign up to set email alerts
|

The 6 August 2010 Mount Meager rock slide-debris flow, Coast Mountains, British Columbia: characteristics, dynamics, and implications for hazard and risk assessment

Abstract: Abstract.A large rock avalanche occurred at 03:27:30 PDT,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 41 publications
(43 reference statements)
5
111
0
Order By: Relevance
“…12. Example of subjective visual calibration using a 3D model (DAN3D) with two-parameter Voellmy rheology to simulate 2010 Mount Meager landslide described by Guthrie et al (2012). Best overall match was achieved using f = 0.05 and = 500 m/s 2 , where best-match (a) deposit depth and (b) flow velocity results intersect (green box).…”
Section: Model Calibrationmentioning
confidence: 99%
See 4 more Smart Citations
“…12. Example of subjective visual calibration using a 3D model (DAN3D) with two-parameter Voellmy rheology to simulate 2010 Mount Meager landslide described by Guthrie et al (2012). Best overall match was achieved using f = 0.05 and = 500 m/s 2 , where best-match (a) deposit depth and (b) flow velocity results intersect (green box).…”
Section: Model Calibrationmentioning
confidence: 99%
“…The result is that continuum models tend to overestimate the amount of spreading during the early stages of motion. A DAN3D simulation of the early stages of the Mount Meager landslide described by Guthrie et al (2012) is shown in Galas et al (2007) based on maximization of ratio of intersection (purple area) and union (blue + red + purple areas) of simulated and observed inundation areas. Perfect fit would correspond to a ratio of 1.…”
Section: Limiting Initial Spreadingmentioning
confidence: 99%
See 3 more Smart Citations